2023
DOI: 10.1162/dint_a_00159
|View full text |Cite
|
Sign up to set email alerts
|

FAIREST: A Framework for Assessing Research Repositories

Abstract: The open science movement has gained significant momentum within the last few years. This comes along with the need to store and share research artefacts, such as publications and research data. For this purpose, research repositories need to be established. A variety of solutions exist for implementing such repositories, covering diverse features, ranging from custom depositing workflows to social media-like functions. In this article, we introduce the FAIREST principles, a framework inspired b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…2022)). We have added I4 as we believe that exporting metadata is a crucial feature in supporting I3, as we are in agreement with the FAIR analysis provided in (D'Aquin et. al.…”
Section: Interoperablesupporting
confidence: 84%
See 1 more Smart Citation
“…2022)). We have added I4 as we believe that exporting metadata is a crucial feature in supporting I3, as we are in agreement with the FAIR analysis provided in (D'Aquin et. al.…”
Section: Interoperablesupporting
confidence: 84%
“…al. 2016), there have been a number of papers which sought to explore and interpret the different metrics (Berman & Crosas 2020); some authors suggested extensions and a tighter interpretation of the thresholds for compliance (D'Aquin et. al.…”
Section: Is My Data Fair?mentioning
confidence: 99%
“…Attention should be paid to maintaining the initial purpose of repositories, i.e., providing open access to research results. However, at the same time, repository operators and managers must take more care of the curation of metadata quality, which means, above all, the assessment and improvement of the FAIRness of their infrastructure [33].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted at this point that the original FAIR specification for data was relatively abstract, potentially leading to different interpretations. Some efforts have been made to further clarify the FAIR principles and even suggest ways to strengthen the original description [1]. This was achieved by examining existing open repositories such as EOSC and providing a deeper examination of how to assess some measure of FAIR for repositories.…”
Section: Application Of Fair Metricsmentioning
confidence: 99%